Florfenicol As a Modulator Enhancing Antimicrobial Activity: Example Using Combination with Thiamphenicol against Pasteurella multocida - Wei, Chia-Fong; Shien, Jui-Hung; Chang, Shao-Kuang; Chou, Chi-Chung (Frontiers in Microbiology, 2016)
Synergistic effects between the same class of antibiotics are rarely reported. Our previous study found synergistic-like interaction between florfenicol (FFC) and thiamphenicol (TAP) against Staphylococcus aureus. Here, the enhanced antimicrobial activity was evaluated in 97 clinical isolates of both Gram-negative and Gram-positive bacteria. Susceptible strains were initially identified by checkerboard microdilution assay (fractional inhibitory concentration index [FICI] ≤0.625), followed by confirmation of synergism using the time-kill methodology (≥2 log10 CFU/ml reduction). In all, 43% of Pasteurella multocida tested were susceptible to the enhanced bactericidal effect. In chicken fowl cholera models, FFC and TAP combination at much lower dosage that is correspondent to their MIC deduction provided maximum protection in vivo. Furthermore, synergistic combination of FFC with oxytetracycline (OTC) against Pseudomonas aeruginosa in vitro was also demonstrated. Based on the enhanced uptake of TAP and OTC, FFC presumably elicits enhanced antimicrobial activity in an orderly manner through alteration of bacterial membrane permeability or efflux systems and subsequent increase of intracellular concentration of the antibiotics used in combination. Results of ethidium bromide accumulation assay and RNA-seq showed little evidence for the involvement of efflux pumps in the synergy but further investigation is required. This study suggests the potentiality of a novel combination regimen involving FFC as an initiating modulator effective against both Gram-positive and Gram-negative bacteria depending on the antibiotics that are combined. The observed improvement of bacteriostatic effect to bactericidal, and the extended effectiveness against FFC-resistant bacterial strains warrant further studies.